Kontribusi Pajak Daerah dan Retribusi Daerah terhadap Pendapatan Asli Daerah (PAD) Kabupaten Lamongan Tahun Anggaran 2018 - 2023 - Nabilatun Nihayatuz Zuhuriyyah; Hastanti Agustin Rahayu (CV. ALIM'SPUBLISHING, 2025)
This study aims to analyze the impact of local taxes and regional levies on Original Local Revenue (PAD) in Lamongan Regency from 2018 to 2023. The main issue addressed is the fluctuation in the contribution of local taxes and regional levies to PAD, reflecting the region's financial independence. A quantitative approach was employed, utilizing secondary data from financial reports and government documents. The findings reveal that local taxes have a significant positive effect on PAD, while regional levies show more variable impacts. This research contributes new insights by comparing the effectiveness of these revenue sources over time and identifying challenges in levy collection. The conclusion emphasizes the importance of enhancing taxpayer compliance and optimizing collection systems to increase PAD. Recommendations for future research include exploring innovative strategies for tax and levy management and analyzing the impact of economic conditions on revenue generation.